2018
DOI: 10.22270/jddt.v8i4.1812
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evaluation of Solanum Viarum Dunal Leaves Extract for Analgesic and Antipyretic Activities

Abstract: The family Solanaceae consists of many plants, one of them is Solanum viarum Dunal. This plant contains chemical constituents like Solasodine which is found in many plants of Solanaceae family. The Solasodine have many medicinal properties and used as cardiotonic, antifungal, antispermatogenic, antiandrogenic, immunomodulatory, anticancer, anti-inflammatory, antinociceptive and as antipyretic. The study was carried out to ascertain analgesic and antipyretic activity of ethanolic extract of Solanum viarum Dunal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…In addition, as can be seen in Tables 3 and 4, other bioactive compounds were identified in S. viarum extracts (Table 5). The findings of chemical constituents corroborate that described by Kausar and Singh (2018) when studying the leaves of S. viarum, such as solasodine and quinic acid. Braguini et al (2018) reported toxicity of S. viarum fruits against Artemia salina.…”
Section: Chemical Compositionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, as can be seen in Tables 3 and 4, other bioactive compounds were identified in S. viarum extracts (Table 5). The findings of chemical constituents corroborate that described by Kausar and Singh (2018) when studying the leaves of S. viarum, such as solasodine and quinic acid. Braguini et al (2018) reported toxicity of S. viarum fruits against Artemia salina.…”
Section: Chemical Compositionsupporting
confidence: 88%
“…The compound milbemycin is reported to be an antiparasitic (Hugar and Londonkar, 2017) and Martín et al (2017) attributed antiviral action to cytidine, which is a pyrimidine core compound that plays a vital role in biological activities such as antifungal. The compound solasodine is a highly toxic glycoalkaloid commonly found in the Solanaceae family, described by some authors (Al et al, 2016;Kausar and Singh, 2018;Patel et al, 2013;Yuan et al, 2017). Zeng et al (2009) reported quinic acid anti-inflammatory activity.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the synergistic or antagonistic interaction of the compounds identified by Confortin et al [8,9] should also be relevant due to their interesting bioactivities. In this respect, soalsodine was described with high toxicity [61,62]; quinic acid was reported to have anti-inflammatory potential [49,63]; celidoniol, has antibacterial, anti-inflammatory, and pesticidal action [64][65][66][67]; and integerrimine and senecionine are considered pyrrolizidine alkaloids [68]. However, the mode of action of allelochemicals, including the alkaloid compounds highlighted in this study, remains poorly comprehended.…”
Section: Herbicidal Activity In Pre-emergence Testsmentioning
confidence: 96%